2009
DOI: 10.1002/asna.200811187
|View full text |Cite
|
Sign up to set email alerts
|

New magnetic field measurements of β Cephei stars and slowly pulsating B stars

Abstract: We present the results of the continuation of our magnetic survey with FORS 1 at the VLT of a sample of B-type stars consisting of confirmed or candidate β Cephei stars and Slowly Pulsating B (hereafter SPB) stars, along with a small number of normal B-type stars. A weak mean longitudinal magnetic field of the order of a few hundred Gauss was detected in three β Cephei stars and two stars suspected to be β Cephei stars, in five SPB stars and eight stars suspected to be SPB stars. Additionally, a longitudinal m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 35 publications
3
92
3
Order By: Relevance
“…Improved agreement between observation and theory may be achieved when tailored abundances are used for the stellar evolution models, see also the previous footnote. 4 A magnetic field is present also in HD 74575 (Hubrig et al 2009). ( Fig.…”
Section: Observational Constraintsmentioning
confidence: 91%
“…Improved agreement between observation and theory may be achieved when tailored abundances are used for the stellar evolution models, see also the previous footnote. 4 A magnetic field is present also in HD 74575 (Hubrig et al 2009). ( Fig.…”
Section: Observational Constraintsmentioning
confidence: 91%
“…In particular, the six reported detections of a field in HD 16582 all have decreased below the 3σ significance limit, although one measurement not originally claimed as detection by Hubrig et al (2009a), on MJD = 54 343.259, has risen to the apparently significant value of −104 ± 19 G. A single ESPaDOnS field measurement detects no trace of a field with B z uncertainty of 10 G (Silvester et al 2009). While it is still possible that a field might be present in HD 16582, this must certainly be regarded at present as -at best -extremely uncertain.…”
Section: β Cephei Pulsators and Slowly Pulsating B Starsmentioning
confidence: 99%
“…If these results were confirmed, they would be quite important; such high incidence of detected fields would strongly suggest that magnetism is intrinsically connected with the pulsation phenomenon in early B-type stars, as it is in the cool rapidly oscillating Ap (roAp) stars. Hubrig et al (2006a) and Hubrig et al (2009a) have reported discovery of a field in the β Cep star ξ 1 CMa = HD 46328, based on altogether 13 detections at approximately the 6 or 7σ level.…”
Section: β Cephei Pulsators and Slowly Pulsating B Starsmentioning
confidence: 99%
“…Finally, we point out that Hubrig et al (2011) obtained and analysed spectropolarimetric time series observations taken with the SOFIN échelle spectrograph at the 2.56 m Nordic Optical Telescope, after the discovery of a magnetic field in the star (Hubrig et al 2009). From their 13 data points, three dominant peaks emerged in the periodogram, with the highest peak at 0.072 d −1 .…”
Section: Summary Of Observational Constraintsmentioning
confidence: 99%